Expressed breast milk feeding: knowledge and attitude of employed mothers - Shabbir F,; Nina H,; Lim, ZY; Amelia AR,; Nor Ain MZ,; Shareena Ishak,; Rohana Jaafar, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Appropriate knowledge on expressing, storing and use of breast milk are essential for mothers to continue breastfeeding when they return to work. The objective of this study was to assess the knowledge and attitude of employed mothers towards breast milk expression, storage and usage. This cross-sectional study was conducted among 300 full-time employed mothers who delivered at a tertiary hospital in Kuala Lumpur, Malaysia. A content-validated questionnaire consisting of 28 questions testing knowledge and nine questions assessing attitude was used. The highest possible scores for knowledge and attitude were 28 and 45, respectively. The mean score for knowledge was 20.47 (SD 4.06). Mothers who scored ≥ 21 (≥75% of maximum score) were categorized as having “good knowledge” while those who scored <21 were considered to have “poor knowledge”. One hundred and seventy (57%) mothers had good knowledge. Good knowledge was significantly associated with Malay ethnicity, tertiary education, multiparity status and prior breastfeeding experience. Two hundred and nineteen (73%) mothers had a positive attitude (scored ≥34). Malay ethnicity, tertiary education, multiparity status, prior experience in giving expressed milk and feasibility of expressing breast milk at the workplace were significantly associated with a positive attitude. More than half of the mothers had good knowledge, and a higher proportion had a positive attitude towards breast milk expression, storage and usage. Additional support and education should be given to mothers who are: non-Malay, non-tertiary educated and having their first child as these factors were associated with poor knowledge and negative attitude.